Strategic Planning: Shaping Organisation Action or Emerging from Organisational Action? - Tatum Syarifah Adiningrum (Bina Nusantara University, 2012)
Several perspectives have been offered to explain the strategy making process, and also at the same time offered the best strategy remedy. The perspectives of strategy making can be divided into two main perspectives: mechanic and organic. The mechanic perspectives view strategy as ‘posture and plan’ and the main models used are the design model and SWOT. The organic stream gives alternatives views in strategy development that captures the needs of dynamic interaction with environment and emphasis more on strategic change. Both perspectives will be discussed and their compatibility in the current environment is compared. The two approaches have their own logics, and both are valid depending on the situation and environment the organisation in. However, with the globalization, tight competition and changes in government policies and behavior, organisation is expected to be more flexible in responding to changes and keep and open mind and eyes to unforeseen opportunities and threats. Therefore, nurturing conducive environment for emergent strategies seems like a logical thing to do.